If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -5(3 + -2) = z + 1 Combine like terms: 3 + -2 = 1 -5(1) = z + 1 Multiply -5 * 1 -5 = z + 1 Reorder the terms: -5 = 1 + z Solving -5 = 1 + z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-1z' to each side of the equation. -5 + -1z = 1 + z + -1z Combine like terms: z + -1z = 0 -5 + -1z = 1 + 0 -5 + -1z = 1 Add '5' to each side of the equation. -5 + 5 + -1z = 1 + 5 Combine like terms: -5 + 5 = 0 0 + -1z = 1 + 5 -1z = 1 + 5 Combine like terms: 1 + 5 = 6 -1z = 6 Divide each side by '-1'. z = -6 Simplifying z = -6
| -27=2w+3(w-4) | | 9+3p-5t+3= | | 31-7r=-6r-4(1-r) | | -5-2/7x=-1 | | -5-2/7x=25 | | 2(x+3)+5x=12 | | -90=5(2n-8) | | t/-6-8=7 | | 4+1/3y=-5 | | -3/2x-9=6 | | u/9=1 | | 5x/8=2x/3-1 | | 5x+13=9x-39 | | -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 | | -94-x=-12x+49 | | 13x^2-16x=4 | | 4(k+5)=2(9t-2) |